Development of Quick Response Code-Based Teaching Material for Educational Statistics Courses - Nurjannah Nurjannah; Anggy Heriyanti; Andi Baso Kaswar; A. Mutahharah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to develop interactive teaching materials based on Quick Response (QR) codes for the Education Statistics Course at a State Islamic Institute in Sinjai. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was used to ensure the teaching materials' validity, practicality, and effectiveness. The teaching materials and learning videos underwent a validity test, which found that all aspects were valid, scoring 3.58. The media validation was very valid, with an average validator score of 3.68. The developed teaching materials were practical, with an average respondent rating of 92.07%. Respondents also found the teaching materials effective, with a proportion of 89.63%. These teaching materials will provide students with the knowledge and skills required for their final projects, including proposal preparation, research, data analysis, and thesis compilation. The hope is that these materials will improve the quality of education statistics learning and research, making students more competitive. In conclusion, this research successfully developed interactive teaching materials based on QR codes for the Education Statistics Course, which were found to be valid, practical, and effective.